STUDENTS’ ABILITY WITH GUARDIAN PERSONALITY TYPE TO PRESENT MATHEMATICAL STATEMENTS IN GRAPHS AT CARTESIAN COORDINATE SYSTEM - Sayekti Dwiningrum; Mardiyana Mardiyana; Ikrar Pramudya (Proceedings Education and Language International Conference, 2017)
Reasoning ability is needed by students to understand mathematical concepts. In fact, a lot of students tend to be passive in reasoning. The characteristic of such students will affect their success in learning. One of the important indicators to figure out students’ mathematical reasoning ability is presenting mathematical statements in graphs, and one of students’ characteristics that should be noted by teacher is their personality. According to Keirsey, there are four types of personality. One of the four personality types is guardian. This research is a descriptive qualitative where the subjects are two students with guardian personality; a male and a female students. Both subjects are eighth grade students of junior high school 2 Ngemplak Boyolali who have received straight line equation concept. Students’ ability to present mathematical statements in graphs is explored by interviews based on the outcome of a written test and then analyzed by descriptive qualitative method. The data analysis of the written test and interview conclude that guardian students were able to present mathematics concept in graphs; students were able to draw a straight line at cartesian coordinate system. But, students were only able to draw the line if the points of the coordinate are given in a complete manner. Students were not able to draw the line if they were given only one point and one gradient aid instrument. Students realized that to draw a straight line is needed two points but they were unable to find another point referred to. In conclusion, detailed instructions were needed by guardian students to present mathematical statements in the graphs at cartesian coordinate system. Keywords: Straight Line Equation, Graph, Guardian Personality Type